THE POET WHO TAUGHT HIM TO LOVE HIS COUNTRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines national values, self-awareness, attitude to the people in the works of the People's Poet of Uzbekistan Muhammad Yusuf, and gradually studies the harmony of lyrical melodies in the poems and epics of the poet.